The Clinical Aspect of Adaptor Molecules in T Cell Signaling: Lessons Learnt From Inborn Errors of Immunity - Dinur-Schejter, Yael; Zaidman, Irina; Mor-Shaked, Hagar; Stepensky, Polina (Frontiers in Immunology, 2021)
Adaptor molecules lack enzymatic and transcriptional activities. Instead, they exert their function by linking multiple proteins into intricate complexes, allowing for transmitting and fine-tuning of signals. Many adaptor molecules play a crucial role in T-cell signaling, following engagement of the T-cell receptor(TCR). In this review, we focus on Linker of Activation of T cells (LAT) and SH2 domain-containing leukocyte protein of 76 KDa (SLP-76). Monogenic defects in these adaptor proteins, with known roles in T-cell signaling, have been described as the cause of human inborn errors of immunity (IEI). We describe the current knowledge based on defects in cell lines, murine models and human patients. Germline mutations in Adhesion and degranulation adaptor protein (ADAP), have not resulted in a T-cell defect.